Biofeedback assisted relaxation training and distraction therapy for pain in children undergoing botulinum neurotoxin A injections: A crossover randomized controlled trial. (5th June 2022) - Ostojic, Katarina; Paget, Simon P.; Webb, Annabel; Khut, George P.; Morrow, Angela M.
Abstract: Aim: To compare biofeedback assisted relaxation training (BART) with distraction therapy for pain during botulinum neurotoxin A (BoNT‐A) treatment. Method: This was a crossover randomized controlled trial. Eligible participants were 7 years and older with neurological conditions. Participants were randomized to receive BART or distraction during their first BoNT‐A treatment, followed by the alternative intervention in their subsequent BoNT‐A treatment. BART was delivered via BrightHearts, an interactive heart‐rate‐responsive application. Outcomes were pain (Faces Pain Scale – Revised), fear (Children's Fear Scale), and anxiety (numerical rating scale, State–Trait Anxiety Inventory). Demographics, paired t ‐tests, and linear mixed models were used to compare outcomes. Results: Thirty‐eight participants (mean [SD] age 13 years 5 months [3 years 4 months], 20 males, 34 with cerebral palsy) completed both interventions. There were non‐significant differences in overall pain (mean difference − 0.05, 95% confidence interval [CI] −0.91 to 0.80, p = 0.902) and worst pain (mean difference 0.37, 95% CI −0.39 to 1.13, p = 0.334) when using BART and distraction therapy. There were non‐significant differences in fear and anxiety between interventions. Younger age, heightened pre‐procedural state anxiety, and Gross Motor Function Classification System levels III and IV were associated with poorer outcomes ( p < 0.05). Participants who received BART before distraction therapy reported lower pain and anxiety scores during both BoNT‐A treatments ( p < 0.05). Interpretation: Children reported similar pain when using BART and distraction therapy. Those who used BART before distraction therapy reported lower pain and anxiety during both treatments. What this paper adds: Children reported similar pain (overall; worst) when using biofeedback assisted relaxation training (BART) and distraction therapy. Children who used BART before distraction therapy reported lower pain and anxiety over both botulinum neurotoxin A treatments. Younger age, pre‐procedural state anxiety, and Gross Motor Function Classification System levels III and IV predicted a worse pain experience. Distraction therapy and BART were acceptable non‐pharmacological interventions for procedural pain management. What this paper adds: Children reported similar pain (overall; worst) when using biofeedback assisted relaxation training (BART) and distraction therapy. Children who used BART before distraction therapy reported lower pain and anxiety over both botulinum neurotoxin A treatments. Younger age, pre‐procedural state anxiety, and Gross Motor Function Classification System levels III and IV predicted a worse pain experience. Distraction therapy and BART were acceptable non‐pharmacological interventions for procedural pain management. We compared biofeedback assisted relaxation training (BART) with distraction therapy for pain during botulinum neurotoxin A treatment. Children reported similar pain when using BART and distraction therapy. Those who used BART before distraction therapy reported lower pain and anxiety during both treatments. This original article is commented on by Friedrichsdorf on pages 1437–1438 of this issue.